Relationship Between Asperities and Velocity Pulse Generation Mechanism - Han, Lu; Tao, Zhengru; Cao, Zelin; Tao, Xiaxin (Frontiers in Earth Science, 2022)
Near-fault ground motion records often capture instances of pulse-like behavior, where a burst of energy is expressed as large wave amplitude that occur over short time. The pulse-like ground motion can cause serious damage to long-period structures. Using numerical simulations of near-fault ground motions, we analyze the mechanisms involved in the generation of velocity pulses in the 1994 Northridge Earthquake and the 1979 Imperial Valley Earthquake. The degree to which the asperities affect the pulse generation process is investigated by identifying individual velocity pulses from the superposition process of sub-fault ground motions. Pulse indicators Ep and PGVp represent pulse characteristics in the ground motions at the stations located near the epicenter (near-epicenter stations) and the stations located along the forward rupture propagation direction of the asperity (rupture-direction stations), respectively. To observe the effects of the asperities and the spatial relationship between the pulse-like ground motion stations and the asperities, we determine the contribution of the sub-fault motions to the pulse amplitude. Furthermore, we analyze the pulse indicators and the frequency components using simulated ground motions from two different slip distributions. The near-epicenter station ground motions, produced by homogeneous slip distribution, exhibit higher pulse amplitude and more concentrated low-frequency energy than those generated by the inhomogeneous slip distribution. The rupture-direction station ground motions, produced by inhomogeneous slip distribution, present higher pulse amplitude and more concentrated low-frequency energy than those generated by the homogeneous slip distribution. Our analysis reveals that during the fault rupture process, the pulse energy and the pulse amplitude are influenced by both the slip distribution on the fault plane and the spatial relationship between the seismic station and the asperity.